Diminishing Water-Intake may have Pragmatic Aspects in Lambs Fed on Pelleted Complete Diet and Reared under Thermo-Neutral Condition - M. O. Sanni; E. M. Samara; K. A. Abdoun; M. A. Al-Badwi; M. A. Bahadi; A. A. Al-Haidary (Tropical Animal Science Journal, 2022)
Some basic questions regarding sheep’s ability to tolerate different levels of water intake (WI), especially when fed on a pelleted-complete diet (PCD) and reared under comfortable climatic conditions, are still open. To investigate the direct influence of different levels of WI in sheep fed PCD and reared under such conditions on the lambs' physiological (performance, thermal, blood and urine) status, 24 healthy male growing Najdi lambs were exposed under thermo-neutral conditions to three levels of WI (100%, 67%, and 33% of their ad libitum WI or water requirement) for 6 weeks. Meteorological, production performance, thermo-physiological, as well as blood and urine biochemical measurements, were all determined. The obtained findings clearly substantiate that reducing the level of water intake (p<0.05) produced tangible effects in both 67-WI and 33-WI lamb groups. However, 67-WI lambs showed resilience to limited water availability by inducing proportional physiological responses in their production performances, body temperatures, blood metabolites, and renal function but within the homeostatic ranges similar (p>0.05) to 100-WI lambs. Results collectively signify that diminishing WI up to 33% in lambs (fed on PCD and reared under comfortable conditions) would ensure that water is adequately conserved under prevailing water scarcity and can be implemented without compromising their homeostatic functions. Such applied approaches can consequently have a pragmatic aspect through improving water management approaches required for PCD-based sheep production under water scarcity conditions, which is crucial to economical animal production and responsible animal stewardship. Feasibility studies are thereby highly recommended.